Making Six Sigma last : managing the balance between cultural and technical change - Eckes, George, 1954- (John Wiley, 2001)
""Making Six Sigma Last is the most practical and helpful resource that I have seen on this subject. George's charisma and charm spill over into this interesting and entertaining book. Using one of George's many analogies, 'this is an upper-deck shot, ' and combined with his first book should become the benchmark for Six Sigma learning.""--Dan Porter, Chairman and CEO, Wells Fargo Financial""An energetic, step-by-step exploration filled with interesting and entertaining examples of real-world business experiences. Making Six Sigma Last is a powerful action plan for managers!""-Guenter Bu